Paracetamol or ibuprofen? A pilot study comparing rescue therapy for PDA in preterm infants within the first month - Mukherjee, Arindam; Gupta, Anupam; Fullwood, Catherine; Gottstein, Ruth (Frontiers in Pediatrics, 2026)
Aims and objectivesTo evaluate a study design aimed to assess the effectiveness and safety of IV paracetamol compared to IV ibuprofen for rescue treatment of clinically and hsPDA in preterm infants.SettingThis pilot randomised controlled trial was conducted in the regional neonatal intensive care unit in Manchester, UK, between September 2021 and August 2023.Patients and methodsThe study recruited preterm infants (gestational age <32 weeks or birth weight <1,500 g) diagnosed with hsPDA via echocardiogram and presenting with signs and symptoms of PDA. Participants were randomised to receive either paracetamol or ibuprofen within the first 28 days of life. The primary outcome was closure or reduction to non-hsPDA, while secondary outcomes included the incidence of short- or medium-term complications of prematurity, such as BPD, NEC, IVH, and ROP. Adverse effects of medications were also reviewed to ensure safety. As part of the pilot design, recruitment, retention and data completeness were evaluated.ResultsA total of 32 infants were recruited within a 2-year study period. Overall, both groups of infants showed similar baseline characteristics, although ibuprofen group had slightly smaller and sicker infants, despite randomisation. A high proportion of eligible babies were recruited (91.4%) and completed the trial. Post-intervention, 37.5% (16.1–50.0%) of infants in the paracetamol group converted to non-hsPDA, compared to 25.0% (7.3–52.4%) in the ibuprofen group (p = 0.704). There were no statistically significant differences between the two groups in short- or medium-term complications of prematurity or adverse effects. The trial also demonstrated feasibility by achieving the desired sample size in the given time frame with 91% consent and 100% completion.ConclusionsThe PAIR (Paracetamol and Ibuprofen Research) trial indicated no differences in efficacy or safety between the two treatments. A larger study is required to validate the findings; this trial has demonstrated the feasibility of such a study.Clinical Trial Registrationclinicaltrials.gov, identifier NCT04986839.